Pengaruh Kepedulian Lingkungan (Enviromental Concern) dan Paradigma Lingkungan Baru (New Environmental Paradigm) terhadap Intensi Perilaku Pro Lingkungan (Behavioral Intention) Siswa - Indah Praminingsih; I Made Putrawan; Ade Suryanda (IJEEM - Indonesian Journal of Environmental Education and Management, 2021)
The environment is fairly critical, and it can be said that the main cause of environmental damage is humans. Therefore concern is needed to overcome environmental problems so that it will change the new environmental paradigm and bring up the behavioral intention that will be used as behavior. This research is aimed to determine the effect of environmental concern and new environmental paradigm toward behavioral intention that students have. Research conducted at SMA Negeri 71 Jakarta on the Semester I of 2019/2020 school year. The method used is a survey method through causal studies and analyzed by path analysis. The sample were 96 students of class XII MIPA. The instrument used are environmental concern (27 items, reliability 0.773), new environmental paradigm (30 items, reliability 0.858) and behavioral intention (27 items, reliability 0.736). Based on these results, it can be concluded that new environmental paradigm cannot be a mediator of variables between environmental concern and behavioral intention on students.